2020
DOI: 10.2147/ccide.s241015
|View full text |Cite
|
Sign up to set email alerts
|

<p>Calcium Silicate-Based Cements as Root Canal Medicament</p>

Abstract: Purpose: This study aims to retard the setting reaction of CSC by mixing it with 2% chlorhexidine gel (CHX) which will be used as an intracanal medicament, and to evaluate the removal of the experimental medicaments from the root canal. Materials and Methods: White Portland cement, white ProRoot MTA and Biodentine were mixed with 2% CHX. The setting time, flowability and film thickness of the CSC/CHX mixture (experimental medicaments) were assessed and measured following the standards of ISO specification. Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Most studies in the field of endodontic regeneration have been limited to case reports or case series and the best intracanal medicament with the lowest cytotoxicity and highest antimicrobial property is yet to be determined. An in vitro study by Mahmoud et al [ 17 ] showed the possibility of using MTA as an intracanal medication by mixing it with 2% CHX to slow down its setting time. The calcium ion release and flowability of this mixture was shown to exceed that of CH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies in the field of endodontic regeneration have been limited to case reports or case series and the best intracanal medicament with the lowest cytotoxicity and highest antimicrobial property is yet to be determined. An in vitro study by Mahmoud et al [ 17 ] showed the possibility of using MTA as an intracanal medication by mixing it with 2% CHX to slow down its setting time. The calcium ion release and flowability of this mixture was shown to exceed that of CH.…”
Section: Discussionmentioning
confidence: 99%
“…The original goal of this study was to investigate the potential cytotoxicity of retro-MTA mixed with CHX as an intracanal medicament and our results showed that its cytotoxicity increased significantly over time. This may be due to the fact that MTA has strong alkalizing activity [ 17 ] which can have an adverse effect on cell viability [ 28 ]. According to the result of the current investigation, viability percentage in the MTA+CHX group after 7 days was less than 30%, indicating that the mixture was highly cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracanal application of calcium silicate-based cement (white Portland cement, white ProRoot MTA and Biodentine) with chlorhexidine as a vehicle showed higher calcium ion release compared to calcium hydroxide during the 14 days period. The addition of 2% chlorhexidine extended the setting time up to 84 days and consequently facilitated the removal of medicament [36].…”
Section: In-vitro Studiesmentioning
confidence: 99%
“…[ 1 ] Merely shaping the canal is insufficient for thorough bacteria elimination, prompting the recommendation of a combined approach involving irrigation, instrumentation, and intracanal medication. [ 2 ] Studies have shown that a significant proportion, ranging from 40% to 60%, of cultivable bacteria remains present in the root canals, even after undergoing irrigation with sodium hypochlorite. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%